EFEKTIFITAS PENURUNAN KADAR LOGAM BERAT FE DAN PB DALAM AIR MELALUI PENAMBAHAN BIOKOAGULAN MELALUI ALAT FILTRASI BERBASIS TEKNOLOGI SEL SURYA - Meita Rezki Vegatama; Ain Sahara; Muhammad Ashar Ramadhan (PETROGAS: Journal of Energy and Technology, 2022)
Water is an essential source of needs for all living things and human life. For the category that can be consumed, the water must meet several criteria such as chemical, physical, bacteriological and radioactive. From the category of chemical quality, heavy metal is one of the parameters that must meet the standard for the category of clean drinking water, including Fe and Pb. In this study, data were taken three times to simulate the use of this water filter which will be used to analyze the levels of heavy metals Fe and Pb. The results of the first experiment before filtration and the addition of bio coagulants, Fe levels were 0.083 mg/L and Pb levels were 0.0062 mg/L to 0.055 mg/L at Fe levels and 0.0043 mg/L at Pb levels, respectively. The next data is seen in the second simulation, the results of the analysis of Fe levels before the addition of bio coagulants and filtration are 0.087 mg/L and Pb levels are 0.0069 mg/L, but after treatment, Fe levels and Pb levels become 0.063 mg/L and 0.0059 mg/L. Furthermore, in the third analysis, Fe levels before treatment were 0.091 mg/L and after treatment became 0.072 mg/L, while the Pb levels at the beginning before treatment were 0.0084 mg/L to 0.0066 mg/L.